Outcomes and disease management in patients with atrial fibrillation ≥80 years: data from a consecutive 11‐year real‐world registry - Yildirim, Mustafa; Milles, Barbara Ruth; Hund, Hauke; Biener, Moritz; Müller-Hennessen, Matthias; Frey, Norbert; Katus, Hugo; Giannitsis, Evangelos; Salbach, Christian (Journal of the American Heart Association, 2025)
Background - As the population ages, atrial fibrillation (AF) prevalence increases, but data on optimal oral anticoagulation (OAC) in patients ≥80 years remain limited. This study tested whether direct OACs offer comparable benefits to vitamin K antagonists in patients ≥80 years with AF presenting to the emergency department. - Methods - This single‐center retrospective all‐comer study used data from the Heidelberg Registry of Atrial Fibrillation, including patients with AF presenting to the emergency department of the University Hospital of Heidelberg from June 2009 until March 2020. Data were analyzed by age for outcomes and risk factors for predefined end points. - Results - Patients ≥80 years comprised 32.2% of AF cases. Hazard ratios (HRs) for the primary end point (all‐cause mortality, stroke, or myocardial infarction) and secondary end point (including major bleeding) were 3.09 (95% CI, 2.73-3.21) and 2.96 (95% CI, 2.73-3.21) for patients ≥80 years, compared with younger patients. Anticoagulation rates were slightly lower in patients ≥80 years (67.9% versus 70.5%, P=0.0070). OAC use, particularly the use of direct OACs, increased over time. Patients ≥80 years without OACs had higher HRs for primary (3.48 [95% CI, 3.07-3.94]) and secondary end points (3.23 [95% CI, 2.86-3.64]) compared with those with OACs. Vitamin K antagonist use was linked to higher HR for stroke or major bleeding events (HR, 1.25 [95% CI, 1.05-1.50]), rising to 1.64 (95% CI, 1.34-2.01) after excluding reduced direct OAC doses. - Conclusions - Our data highlight patients ≥80 years as an important and vulnerable subpopulation of patients with AF, where evidence for optimal OAC therapy remains conflicting. - Registration - URL: https://www.clinicaltrials.gov; Unique identifier: NCT05995561.
Online veröffentlicht: 18 February 2025
Gesehen am 22.07.2025